Foliar cuticles of species of Persea subg. Eriodaphne (Lauraceae) - Moraes, Pedro Luis Rodrigues de [UNESP]; Trinca, Mayra Deltreggia [UNESP] (Magnolia Press, 2022)
The American species of Persea are divided in two subgenera, Persea subg. Persea and P. subg. Eriodaphne, which form a monophyletic group. In this study we analysed leaf cuticle characters of 220 collections of 54 species of Persea, 48 of them belonging to the P. subg. Eriodaphne, two belonging to the P. subg. Persea, and another four formally unplaced. A dichotomous identification key was built from a matrix of eight leaf cuticle qualitative characters and 30 states, most of them illustrated here for the first time by light and scanning electron microscopy, which allowed us to distinguish these taxa.
Keywords: Laurales; leaf morphology; Neotropics; stomata; taxonomy